Reverse Engineering (Pengambilan Data Dan Kalibrasi 3D Dengan Menggunakan Kamera Digital) - listianto, choirul (2016)
ABSTRACT This study aims to reverse engineering or Making the CAD drawing three-dimensional (3D) by way of processing digital data by using software Autodesk 123D Catch for processing digital data, Autodeks Meshmixer for editing images of three-dimensional (3D), and DDS Solidworks to capture data required. The research object is a cube and a triangular pyramid shaped objects. The study also aimed to know the precision of digital image processing results with the first object. This study used two methods: Method A by shooting randomly or not using the specified angle, and method B with shooting with adjustable angles. In the image is taken in a circle 360° with sliding angle 22.50°. From the data of the study showed that the results obtained from the reverse engineering of digital image processing is a deviation in the cube object, the largest is -1.60 mm (-1.60%) contained in the cube without corners and smallest is 0.00 (0.00%) mm contained in a cube by using corner. For a triangular pyramid the largest deviation is 1.66 mm (0.96%) contained in the pyramid without angles, and the smallest is -0.37 (-0.21%) contained in the pyramid with no angles.